Teacher Quality and Student Inequality - Mansfield, Richard K. (Journal of Labor Economics, 2015)
This paper uses eleven years of administrative data from North Carolina public high schools to examine the extent to which the allocation of teachers within and across public high schools is contributing to inequality in student test score performance. The existence of nearly 3,500 teacher transfers allows separate identifica-tion of each teacher’s quality from other school-level factors. I find that teaching quality is fairly equitably distributed both within and across high schools: students among the bottom (top) decile of a student back-ground index are taught by teachers who are, on average, at the 41st (57th) percentile of the value-added distribution. I have greatly benefited from the input of Joseph Altonji, as well as Fabian Lange, Melissa Tartari, Costas Meghir, Lisa Kahn, Amanda Kowalski, and several anonymous referees. I also thank Mark Klee, Matthew Johnson, Priyanka